The Evolution of Public Administration Paradigms and Their Influence on Public Service Delivery: A Review - Judijanto, Loso (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Developments in public administration have seen a significant paradigm shift as the complexity of public demands and the dynamics of government governance have increased. This study aims to examine and analyse the evolution of public administration paradigms and their implications for the delivery of public services in the contemporary era. The method employed is a qualitative literature review of academic articles published since 2020, focusing on the main paradigms of public administration, including Old Public Administration (OPA), New Public Administration (NPA), New Public Management (NPM), New Public Services (NPS), New Public Governance (NPG), Public Value Management (PVM), Digital Era Governance (DEG), and the Whole of Government (WoG) approach. The findings indicate that each paradigm has its own contributions and limitations in improving service quality, accessibility, accountability, and public trust. No single paradigm was found to be fully capable of addressing all the challenges of modern public service. Therefore, this study emphasises the importance of an integrative and adaptive approach that takes into account the social, institutional, and technological contexts in public administration management to meet the increasingly complex expectations of the public.